2023
DOI: 10.1021/acsinfecdis.2c00567
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signatures of the Eagle Effect Induced by the Artificial Siderophore Conjugate LP-600 in E. coli

Abstract: Achieving cellular uptake is a central challenge for novel antibiotics targeting Gram-negative bacterial pathogens. One strategy is to hijack the bacterial iron transport system by siderophore-antibiotic conjugates that are actively imported into the cell. This was realized with the MECAM-ampicillin conjugate LP-600 we recently reported that was highly active against E. coli. In the present study, we investigate a paradoxical regrowth of E. coli upon treatment of LP-600 at concentrations 16–32 times above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…A few atypical growth phenotypes have been reported for CRAB isolates exposed to cefiderocol, including trailing and paradoxical growth/“Eagle effect” (broth) and microcolonies (disk), which are well known to complicate the endpoint reading of cefiderocol susceptibility tests. These growth phenotypes are not unique to cefiderocol and have also been reported for other antibiotics, including a siderophore conjugate ( 36 , 37 , 44 46 ).…”
Section: Discussionsupporting
confidence: 58%
“…A few atypical growth phenotypes have been reported for CRAB isolates exposed to cefiderocol, including trailing and paradoxical growth/“Eagle effect” (broth) and microcolonies (disk), which are well known to complicate the endpoint reading of cefiderocol susceptibility tests. These growth phenotypes are not unique to cefiderocol and have also been reported for other antibiotics, including a siderophore conjugate ( 36 , 37 , 44 46 ).…”
Section: Discussionsupporting
confidence: 58%
“…Ent is a highly symmetric molecule that lacks a native functionalization handle. Consequently, many efforts by others employed synthetic mimics of Ent to facilitate the installation of conjugation handles, improve conjugate stability, and streamline the synthesis. , Early screening studies of conjugates employing biscatechol and triscatechol analogs showed potential for delivering β-lactam drug cargos but received little follow-up. In recent years, rationally designed SACs employing triscatecholamide Ent mimics where the trilactone core of Ent has been substituted by an alkyl or mesitylene backbone have also shown promise in delivering drug cargos with periplasmic targets. , Nevertheless, it is unclear how these mimics directly compare to the native siderophore scaffold for their uptake and activity. We also consider the instability of the trilactone ring of Ent, to both chemical hydrolysis and potential nonspecific enzymatic breakdown (e.g., host esterases).…”
Section: Introductionmentioning
confidence: 99%
“…41−45 In recent years, rationally designed SACs employing triscatecholamide Ent mimics where the trilactone core of Ent has been substituted by an alkyl or mesitylene backbone have also shown promise in delivering drug cargos with periplasmic targets. [37][38][39]46 Nevertheless, it is unclear how these mimics directly compare to the native siderophore scaffold for their uptake and activity. We also consider the instability of the trilactone ring of Ent, to both chemical hydrolysis and potential nonspecific enzymatic breakdown (e.g., host esterases).…”
Section: ■ Introductionmentioning
confidence: 99%
“…comprehensively overviewed the skepticism and optimism of natural and synthetic sideromycins and, indispensably, the prospect of the synthetic conjugates. , In the field of synthetic sideromycins, catecholate conjugated β -lactams, as well as their bioisostere, hydroxypyridone-type derivatives, are among the most intensively studied categories (Figure ). For one thing, the catecholate-based siderophore mimetics have stronger iron affinity even than that of lactoferrin and transferrin, which are responsible for iron transportation in hosts, and this sort of siderophore can retrieve iron from host transferrin. , For another, β -lactam antibiotics are one of the most powerful drug classes of antibacterial agents with a broad antibacterial spectrum . Beyond that, the targets of β -lactam antibiotics, penicillin-binding proteins (PBPs), are located in the periplasm so that only the OM of Gram-negative bacteria is the major barrier which needs to be passed through, making β -lactam antibiotics a promising payload.…”
Section: Introductionmentioning
confidence: 99%